Foreign direct investment and economic growth in developing countries: how relevant are host-country and industry characteristics? - Peter Nunnenkamp; Julius Spatz (Kiel Institute for World Economics (IfW), 2003)
Conclusive evidence supporting the widely held view that developing countries should draw on foreign direct investment (FDI) to spur economic development is surprisingly hard to come by. We raise the proposition that results on the growth impact of FDI are ambiguous because highly aggregated FDI data, used in virtually all previous empirical studies, blur the differences between resourceseeking, market-seeking and efficiency-seeking FDI and ignore the compatibility of different types of FDI with economic conditions prevailing in the host country. Analysing US FDI stocks in major sectors and specific manufacturing industries in a large number of developing countries, we show that positive growth effects of FDI are anything but guaranteed. Rather, hostcountry and industry characteristics as well as the interplay between both sets of characteristics have an important say on the growth impact of FDI in developing countries.
Keywords: F21; 330; foreign direct investment stocks; resource-seeking; market-seeking and efficiency-seeking FDI; host-country characteristics; Direktinvestition; Amerikanisch; Wirtschaftswachstum; Entwicklung; Branche; Standortfaktor; Schätzung; Entwicklungsländer